STRUKTUR DAN KOMPOSISI TEGAKAN HUTAN DI PULAU SELIMPAI KECAMATAN PALOH KABUPATEN SAMBAS KALIMANTAN BARAT - man, Nyo; kitha, Was; Thamrin, Eddy (Universitas Tanjungpura, 2014)
This study took place in May 2013 for ± 3 weeks was effective in the field, where the data collection phase by observing all kinds of stands of seedlings, saplings, poles and trees found in the plot observer. Where observations made ​​2 lanes and 1 lane observations for drawing diagram forest profile. based on the results of the research area of ​​the island selimpai obtained 29 types of vegetation seedlings, saplings 30 type, 27 type pole and 29 species of trees. vegetation types dominate for seedlings dungur Inp 28.4456, 28.3284 Inp stake temangu type, pole type Inp 44.2834 fir, and tree type to Inp 55.0086 hibiscus. of the results of analysis of vegetation types selimpai constituent island region that is dominant types, for line 1 of mangrove seedlings inp = 25,8889. on line 2 Dungun Inp = 28,4455. mangrove saplings lane 1 Inp = 20,2279, lane 2 found temangu Inp = 28,3383, lane 1 level pole pine (casuarina equitifolia) Inp = 44.2833, on line 2 of mangroves (hizophora mucronata) Inp = 89,0809. and level tree-bute, bute lane 1 Inp = 3,6958, on line 2 hibiscus Inp = 23,5180. from the analysis of the data found that vegetation has a high value is found at the level of the pole with Inp = 89,0809. Keywords: Determine the structure, stand composition, similarity and dissimilarity stands